Facile Synthesis as well as Structural, Raman, Dielectric and Antibacterial Characteristics of Cu Doped ZnO Nanoparticles. Issue 3 (March 2015) - Iqbal, Javed; Safdar, Nauman; Jan, Tariq; Ismail, Muhammad; Hussain, S.S.; Mahmood, Arshad; Shahzad, Shaheen; Mansoor, Qaisar
Abstract : Here, undoped and Cu doped ZnO nanoparticles (NPs) have been prepared by chemical co-precipitation technique. X-ray diffraction (XRD) results reveal that Cu ions are successfully doped into ZnO matrix without altering its wurtzite phase. The single wurtzite phase of ZnO is retained even for 10 wt% Cu doped ZnO sample. It is observed from the electron microscopy results that higher level of Cu doping varies the morphology of ZnO NPs from spherical to flat NPs. Moreover, the particle size is found to increase with the increase in Cu doping level. Raman spectroscopy results further confirm that Cu dopant has not altered the wurtzite structure of ZnO. Impedance spectroscopy results reveal that the dielectric constant and dielectric loss have increasing trend with Cu doping. Cu doping has been found to slightly decrease the bactericidal potency of ZnO nanoparticles.